Administrative Sanctions for Operational Violations of Trans Koetaradja Bus at Perum Damri Banda Aceh - Muklis; Saidi; Badruzzaman (Jurnal Ilmu Multidisiplin, 2022)
The operational readiness of the Trans Bus crew, usually on the punctuality of the bus crew, because they do not follow the existing schedule procedures, this leads to the departure stop and when arriving at the last stop for dropping off passengers. This is subject to administrative sanctions in the form of a Warning Letter (SP). Problem formulation: how are the administrative sanctions for its employees at Perum Damri Banda Aceh?. How is the work safety of the bus crew at Perum Damri Banda Aceh?. Research Objectives: To find out and analyze the administrative sanctions for its employees at Perum Damri Banda Aceh. To find out and analyze the work safety of the bus crew at Perum Damri Banda Aceh. The research method uses a qualitative approach. Data collection techniques are carried out using observation techniques, interviews, documentation studies. The results of the study, minor violation sanctions are given advice for good in the future, previous discipline has not succeeded in changing their behavior. Obey the rules of behavior at work. Demonstrated by doing work in accordance with the position, duties, and responsibilities. Conclusion, the application of administrative sanctions for operational violations of Buses that do not comply with existing rules, apply administrative sanctions because they have to go directly to the field. Lack of awareness of the responsibility of the bus crew towards public service. Efforts made to overcome obstacles in the application of administrative sanctions against operational violations of buses that do not comply with the rules include conducting field inspections to conduct direct inspections or provide verbal warnings.